Dimensional Accuracy of Irreversible Hydrocolloid When Mixed with Disinfectant Solutions - Pathak, B; Parajuli, PK; Basnet, BB (Journal of Nepalese Prosthodontic Society, 2024)
Introduction: Dental impressions, contaminated with blood and saliva are sources of crosscontamination and route for disease transmission. Dental impressions may be decontaminated when disinfectants are incorporated within the impression material, either in the alginate powder or in the mixing liquid. The objective of this study was to investigate the dimensional accuracy of alginate impression material when 1% povidone iodine and 0.1% chlorhexidine were used as mixing liquid. Methods: A total of 69 impressions were obtained from a master model of a stainless-steel ruled block; 23 impressions for each group of water, 1% povidone iodine and 0.1% chlorhexidine, according to the liquid used for mixing alginate powder. After removal and careful inspection, impressions were immediately poured with type IV die stone. Distance between reference points was measured in casts by a travelling microscope. Collected data were entered in Microsoft Excel 2016 and converted into Statistical Package for Social Science (SPSS) version 20.0 for statistical analysis. The data were analyzed using one way ANOVA and post-hoc test. Results: One way ANOVA analysis showed statistically no significant difference (P> 0.05) between different groups with respect to the dimensional change of the casts. Conclusion: The dimensional accuracy of irreversible hydrocolloid impression material was not influenced when 1% povidone iodine and 0.1% chlorhexidine solution were used as mixing liquid instead of water.